Correlations of Osteonectin with other Biochemical parameters in Patients with Rheumatoid Arthritis - Hussein, Mohamed Khaled; Haddad , Namir I. A. (Iraqi Journal of Science, 2025)
Rheumatoid Arthritis (RA) is a long-term autoimmune disorder that causes ongoing inflammation in the joints, starting with smaller joints and gradually spreading to larger ones, with potential complications affecting other parts of the body. The chronic inflammation in the synovial membrane leads to the degradation of cartilage and bone. Osteonectin (SPARC), a protein involved in tissue remodelling, is found to be highly expressed in the cartilage and synovium of individuals with RA, indicating its potential role in the disease process. This research aimed to investigate serum Osteonectin (ON) concentrations as a potential marker of RA disease activity. The study included 58 patients with RA and 30 healthy individuals, divided into three groups: G1 (RA with mild disease activity, n=29), G2 (RA with moderate disease activity, n=29), and G3 (healthy controls, n=30). Clinical information, anthropometric parameters, duration of the disease, treatment type, and Clinical Disease Activity Index score (CDAIs), were recorded. Serum ON levels were measured using the ELISA technique on frozen samples. Statistical analysis involving ANOVA and Pearson's correlation was used.  The results revealed that serum ON levels in G1 and G2 groups were higher than C group (49.29±10.27, 60.13±16.38 and 22.15±5.94) respectively. In G1, a strong negative correlation was found between serum ON levels and weight (r=-0.553, p=0.002). Additionally, positive correlations were noticed between serum ON levels and disease duration (r=0.513, p=0.004), triglycerides (r=0.428, p=0.021), and AST (r=-0.437, p=0.018). In contrast, G2 showed only a moderate negative correlation was observed between serum ON levels and AST (r=-0.437, p=0.018). The elevated levels of ON suggest that its involvement in RA is associated with clinical parameters. Also, ON may has a potential role in disease progression, lipid metabolism, and liver function.